Struktur Skeleton Sirip Kaudal Kompleks Periophthalmus gracilis - Gatot Nugroho Susanto; Fransisca Ressa Utari (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2016)
Cauda of Periophthalmus gracilis rarely used for locomotion in land. The objective is to know skeleton structure of caudal fin complex. Skeleton staining used Alizarin red’s-alcian blue modified from Inouye (1976). Periophthalmus gracilis’s caudal fin complex have 8 os preural centrum, 2 os epural, os parhypural, 5 os hypural and branched lepidotrichia. The caudal used to support movement in land. Periophthalmus gracilis used it for balancing and support in land.